1989
DOI: 10.1099/0022-1317-70-8-1933
|View full text |Cite
|
Sign up to set email alerts
|

'Pathogenesis-related' P1(p14) Protein. Vacuolar and Apoplastic Localization in Leaf Tissue from Tomato Plants Infected with Citrus Exocortis Viroid; in vitro Synthesis and Processing

Abstract: SUMMARYTomato 'pathogenesis-related' Pl(pl4) protein was synthesized in vitro, mRNAs were isolated from leaves showing characteristic symptoms of viroid infection, followed by chromatography on oligo(dT)-cellulose and the poly(A) + fraction was translated with a rabbit reticulocyte lysate system. No significant differences were found between the levels of [3SS]methionine incorporation directed by mRNA preparations from healthy and viroid-infected leaves. Only mRNA from infected leaves incorporated label into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 14 publications
(15 reference statements)
0
22
1
Order By: Relevance
“…Additionally, tobacco cell cultures subjected to osmotic stress also contain inclusion bodies in which osmotin preferentially accumulates (Singh et al, 1987). Unlike the tomato PR proteins Pl(pl4) and P69, which are present in both vacuolar inclusion bodies and intercellular spaces (Vera et al, , 1989a(Vera et al, , 1989b, P23 was not detected in the apoplast. The specific vacuolar compartmentation of P23 is otherwise coincident with what is general for most basic PR proteins described to date (Bol et al, 1990).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Additionally, tobacco cell cultures subjected to osmotic stress also contain inclusion bodies in which osmotin preferentially accumulates (Singh et al, 1987). Unlike the tomato PR proteins Pl(pl4) and P69, which are present in both vacuolar inclusion bodies and intercellular spaces (Vera et al, , 1989a(Vera et al, , 1989b, P23 was not detected in the apoplast. The specific vacuolar compartmentation of P23 is otherwise coincident with what is general for most basic PR proteins described to date (Bol et al, 1990).…”
Section: Discussionmentioning
confidence: 91%
“…Further characterization presented in this work has revealed that tomato PR P23 is a vacuolar protein that seems to be selectively localized in association with inclusion bodies. The nature of these vacuolar structures remains obscure, but we have found them to be present in cells from viroid-infected tissues and absent from healthy ones (Vera et al, 1989a(Vera et al, , 1989b. Additionally, tobacco cell cultures subjected to osmotic stress also contain inclusion bodies in which osmotin preferentially accumulates (Singh et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…electron-dense material in the intercellular spaces and with vacuolar 'inclusion bodies' (29,30). Hence, it was concluded that P14 could be involved in cell degeneration during senescence or pathogenic attack.…”
mentioning
confidence: 99%